P334 Does the circadian clock have a role in the pathogenesis of inflammatory bowel disease (IBD)?. (16th January 2018) - Weintraub, Y; Cohen, S; Dotan, I; Tauman, R; Chapnik, N; Froy, O
Abstract: Background: Sleep dysfunction modifies the immune system and has been implicated as a potential trigger of IBD flares. Sleep dysfunction also alters the synchrony among clock genes leading to disruption of overall circadian regulation. Specifically, in the intestine, it is manifested by increased gut cellular permeability. We hypothesised that changes in mucosal immune balance may be reflected by alterations in the circadian clock and constitute an unattended pathogenic mechanism of IBD. Our aim was to investigate intestinal and systemic clock gene expression (in patients with newly diagnosed IBD and in healthy controls). Methods: Patients and controls were recruited upon diagnostic endoscopic evaluation. Demographics, familial medical history, sleep questionnaires, disease activity indices, and endoscopic scores were recorded. Anthropometric parameters, C-reactive protein (CRP), albumin, haemoglobin (Hb), and fecal calprotectin (Fcal) were measured as well. Peripheral blood and tissue samples were analysed for clock gene (Clock, Bmal1, Cry1, Cry2, Per1, and Per2) expression. Results: Of the 32 participants recruited (age 8–25 years, median: 16.1), 14 had newly diagnosed IBD and 18 were healthy controls. Age, gender, sleep questionnaire scores, and time of endoscopy were not statistically different between the groups. Hb, CRP, and Fcal levels were significantly higher in the IBD compared with the healthy controls group ( p < 0.05), while albumin was significantly lower ( p < 0.05). Clock gene expression (Clock, Cry1, Cry2, Per1, and Per2) in WBC was decreased in newly diagnosed IBD patients compared with health controls ( p < 0.05). Similarly, the expression level of the aforementioned genes was lower in inflamed intestinal tissues ( p < 0.05). Interestingly, similar reduction in clock gene expression was seen even in healthy (non-inflamed) intestinal tissue from IBD patients ( p < 0.05). Conclusions: Clock gene expression is reduced in both inflamed and non-inflamed intestinal tissue in patients with newly diagnosed IBD. Moreover, IBD patients show a systemic reduction in clock gene expression. Our findings may lead to new therapeutic approaches and strategies as well as serve as diagnostic tools in IBD.